Advanced Microgrid: Containerized Development Platform - João Marcus S. Callegari; Danilo Iglesias Brandao; Luís Guilherme Monteiro Oliveira; Sidelmo Magalhães Silva; Braz J. Cardoso Filho (Eletrônica de Potência)
This paper presents a containerized development platform suitable for developing and validating advanced microgrids (MGs). Through a collaborative effort involving the Federal University of Minas Gerais (UFMG) within the technical-scientific research project titled Minirrede Oasis-UFMG and the State and Federal government, the Tesla containerized MG emerges as a physical simulation tool on advanced MG projects in both islanded and grid-connected operating modes. Installed at the Tesla Laboratory located in the UFMG School of Engineering, Brazil, Tesla MG is composed of (i) eleven distributed energy resources (DERs), which supply around 33 kW; (ii) one single-phase gas-driven synchronous generator (SG), with a power rating of 11 kW; (iii) one 7.5 kW three-phase diesel-driven SG; and (iv) 30 kVA 4-quadrant programmable AC load and source. All these devices are commercially available off-the-shelf equipment. Photovoltaic modules and different battery technologies are installed outside and inside the container, respectively, with cabling extending to the container to connect these components to the inverters. Hardware-in-the-loop (HIL) platforms for real-time simulations (i.e., Opal RT OP5700 and Typhoon HILs 402 and 604) are also available to support MG research. Experimental results are provided to demonstrate the capabilities of the Tesla MG, specifically focusing on inverter features, power dispatchability in grid-connected mode, and proper operation in islanded mode.